Evaluation of ABCA1 and FNDC3B Gene Polymorphisms Associated With Pseudoexfoliation Glaucoma and Primary Angle-Closure Glaucoma in a Saudi Cohort - Kondkar, Altaf A.; Sultan, Tahira; Azad, Taif A.; Osman, Essam A.; Almobarak, Faisal A.; Lobo, Glenn P.; Al-Obeidan, Saleh A. (Frontiers in Genetics, 2022)
Objective: It is plausible that common disease mechanisms exist in glaucoma pathophysiology. Accordingly, we investigated the genetic association of two previously reported primary open-angle glaucoma (POAG)-related gene polymorphisms, rs2472493 (A>G) in ABCA1 and rs7636836 (C>T) in FNDC3B, in primary angle-closure glaucoma (PACG) and pseudoexfoliation glaucoma (PXG). Methods: TaqMan genotyping was performed in a total of 442 subjects consisting of 246 healthy controls, 102 PACG patients, and 94 PXG patients. Statistical evaluations were performed to detect allelic and genotype association of the variants with the disease and clinical variables such as intraocular pressure (IOP) and cup/disc ratio. Results: Overall, there was no allelic/genotype association of these variants in PACG and PXG. However, rs7636836[T] allele significantly increased the risk of PXG among men (p=0.029, odds ratio [OR]=2.69, 95% confidence interval=1.11-6.51). Similarly, rs2472493 and rs7636836 genotypes also showed significant association with PXG among men in over-dominant model (p=0.031, OR=1.98, 95% CI=1.06-3.71) and co-dominant model (p=0.029, OR=2.69, 95% CI=1.11-6.51), respectively. However, none survived Bonferroni’s correction. Besides, the synergic presence of rs2472493[G] and rs7636836[T] alleles (G-T) was found to significantly increase the risk of PACG (p=0.026, OR=2.85, 95% CI=1.09-7.46). No significant genotype influence was observed on IOP and cup/disc ratio. Conclusions: Our results suggest that the polymorphisms rs2472493 in ABCA1 and rs7636836 in FNDC3B genes may be associated with PXG among men, and a G-T allelic combination may confer an increased risk of PACG in the middle-eastern Saudi cohort. Further research in a larger population-based sample is needed to validate these findings.